Socioeconomic differences in selection for liver resection in metastatic colorectal cancer and the impact on survival. Issue 10 (October 2018) - Vallance, A.E.; van der Meulen, J.; Kuryba, A.; Braun, M.; Jayne, D.G.; Hill, J.; Cameron, I.C.; Walker, K.
Abstract: Background: Socioeconomic inequalities in colorectal cancer (CRC) survival are well recognised. The aim of this study was to describe the impact of socioeconomic deprivation on survival in patients with synchronous CRC liver-limited metastases, and to investigate if any survival inequalities are explained by differences in liver resection rates. Methods: Patients in the National Bowel Cancer Audit diagnosed with CRC between 2010 and 2016 in the English National Health Service were included. Linked Hospital Episode Statistics data were used to identify the presence of liver metastases and whether a liver resection had been performed. Multivariable random-effects logistic regression was used to estimate the odds ratio (OR) of liver resection by Index of Multiple Deprivation (IMD) quintile. Cox-proportional hazards model was used to compare 3-year survival. Results: 13, 656 patients were included, of whom 2213 (16.2%) underwent liver resection. Patients in the least deprived IMD quintile were more likely to undergo liver resection than those in the most deprived quintile (adjusted OR 1.42, 95% confidence interval (CI) 1.18–1.70). Patients in the least deprived quintile had better 3-year survival (least deprived vs. most deprived quintile, 22.3% vs. 17.4%; adjusted hazard ratio (HR) 1.20, 1.11–1.30). Adjusting for liver resection attenuated, but did not remove, this effect. There was no difference in survival between IMD quintile when restricted to patients who underwent liver resection (adjusted HR 0.97, 0.76–1.23). Conclusions: Deprived CRC patients with synchronous liver-limited metastases have worse survival than more affluent patients. Lower rates of liver resection in more deprived patients is a contributory factor.